(untitled) (International Journal of Engineering and Computer Science, 2015)
This paper designs monitoring and controlling parameters of Plastic Extrusion Blow molding system. This system takes ARM processor as a core and takes CAN bus as communication system by analyzing the human machine interface system. In this Hardware design consist of LPC2138 with ARM7 microprocessor having large memory capacity and CAN communication as Human machine interface control device. In software design Embedded C is transplanted to the ARM core to achieve real time multi task switching. Secondly, GUI is transplanted to display graphics & text. Write the HMI application program task-unit. Finally LPC 2138 communicates to human machine interface system with CAN bus and HMI of the Plastic Extrusion blow molding system is completed.